قراءة في قصيدة الاستنجاد للشاعر أحمد بن عبد الدائم الأنصاري (دراسة تحليلية): قراءة في قصيدة الاستنجاد للشاعر أحمد بن عبد الدائم الأنصاري (Elmergib Journal of Human Sciences, 2025)
This research examines the historical poem by the poet Ahmed bin Abdul Daim Al-Ansari, written following the French attack on Tripoli in 1728 AD, as a literary document that reveals the political and military features of the Ottoman province of Tripoli in the eighteenth century. The findings reveal how the poem embodies the hierarchical relationship between the province and the Ottoman center, the extent of awareness of technological disparities with European powers, the role played by religious discourse in strengthening political legitimacy, and the role of poetry as an effective means of political communication to convey the concerns of the peripheries to the center.